2020
DOI: 10.3390/ijerph17041379
|View full text |Cite
|
Sign up to set email alerts
|

Migration, Stress and the Challenges of Accessing Food: An Exploratory Study of the Experience of Recent Afghan Women Refugees in Adelaide, Australia

Abstract: This study explored the migration and food experiences of Afghani women refugees residing in Adelaide, South Australia for 2 years or less. In-depth semi-structured qualitative interviews were conducted with 10 women between May and September 2017. The data were thematically analysed, and the Social Determinants of Health Framework was used to discuss the findings. Five key themes emerged from the data. In the transition country (Iran/Pakistan), respondents experienced (i) trauma, discrimination and exclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 37 publications
2
30
0
14
Order By: Relevance
“…These transition country experiences may also be traumatic and impact crisis migrant family health outcomes. For example, qualitative work with Afghani women who settled in Australia found that many faced violence, exclusion, and discrimination from other refugee groups and native peoples during their time in refugee camps in Pakistan (Kavian et al., 2020). Additionally, many Rohingya refugee families have made Bangladesh or Malaysia their country of “first asylum,” but may continue on to other countries or return to Myanmar when it is safe to do so (Shaw et al., 2020).…”
Section: Extrafamilial Contexts Of Migration Stressmentioning
confidence: 99%
“…These transition country experiences may also be traumatic and impact crisis migrant family health outcomes. For example, qualitative work with Afghani women who settled in Australia found that many faced violence, exclusion, and discrimination from other refugee groups and native peoples during their time in refugee camps in Pakistan (Kavian et al., 2020). Additionally, many Rohingya refugee families have made Bangladesh or Malaysia their country of “first asylum,” but may continue on to other countries or return to Myanmar when it is safe to do so (Shaw et al., 2020).…”
Section: Extrafamilial Contexts Of Migration Stressmentioning
confidence: 99%
“…However, compared to the expansion of mobile phones in Pakistan, there have been 30 million fixed and mobile telephone lines. As the country's population was more than 162.4 million in 2008 [23], the country had 5.37 million fixed telephone lines. The subscription of mobile has surged over 19.6 million, which makes the sector of telecom stronger than ever.…”
Section: Introductionmentioning
confidence: 99%
“…Menetap di kem pelarian atau kawasan perumahan, keadaan hidup populasi orang pelarian dan pencari suaka dicirikan sebagai tidak selesa/kondusif atau 'in poor condition' (Labys, Dreyer & Burns, 2017;Pezerović, Babić & Porobić, 2019). Selain itu, mereka juga tinggal dalam jarak yang dekat di antara satu dengan yang lain atau 'close proximity' (Syam et al, 2019;Kavian et al, 2020). Justeru, banyak kajian terdahulu berkaitan adaptasi populasi ini menekankan cabaran dan isu dalam adaptasi antarabudaya.…”
Section: Adaptasi Antarabudaya Populasi Orang Pelarian Dan Pencari Suakaunclassified